2016
DOI: 10.1128/iai.00630-16
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Arginines at the P-Protein Stalk Binding Site and the Active Site Are Critical for Ribosome Interactions of Shiga Toxins but Do Not Contribute to Differences in the Affinity of the A1 Subunits for the Ribosome

Abstract: The A1 subunits of Shiga toxin 1 (Stx1A1) and Shiga toxin 2 (Stx2A1) interact with the conserved C termini of ribosomal-stalk P-proteins to remove a specific adenine from the sarcin/ricin loop. We previously showed that Stx2A1 has higher affinity for the ribosome and higher catalytic activity than Stx1A1. To determine if conserved arginines at the distal face of the active site contribute to the higher affinity of Stx2A1 for the ribosome, we mutated Arg172, Arg176, and Arg179 in both toxins. We show that Arg17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Previous results indicated that the A1 subunit of Stx2 interacts with the ribosome with higher affinity than the A1 subunit of Stx1 [14]. Conserved 1 subunits for the rib arginines at the P-protein stalk binding site did not contribute to the differences in the affinity of the A osome [32]. We show here that Stx2 holotoxin also interacts with the ribosome with higher affinity than Stx1 holotoxin (Figure 4).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous results indicated that the A1 subunit of Stx2 interacts with the ribosome with higher affinity than the A1 subunit of Stx1 [14]. Conserved 1 subunits for the rib arginines at the P-protein stalk binding site did not contribute to the differences in the affinity of the A osome [32]. We show here that Stx2 holotoxin also interacts with the ribosome with higher affinity than Stx1 holotoxin (Figure 4).…”
Section: Discussionsupporting
confidence: 54%
“…Our recent study showed that point mutations at Arg172 or Arg176 located on the opposite face of the active site (Figure 1 and Figure 3) disrupted the ribosome and ribosomal stalk interaction of Stx1A1 and Stx2A1, but did not affect their depurination activity on RNA, indicating that their active sites were intact and were located on the opposite face of the ribosome binding site [32]. Figure 3 shows the structure of Stx holotoxins in comparison with ricin.…”
Section: Resultsmentioning
confidence: 99%
“…The base change at the depurination site was detected using a reverse primer with adenine at the 3′ terminus and the specificity for detection was enhanced by the inclusion of a secondary mismatch two base pairs 5′ to the adenine. The modified qRT-PCR assay provided a sensitive and highly reproducible measure of the extent of depurination by ricin and Stxs in mammalian cells [ 31 , 32 , 37 , 40 ] and in yeast [ 31 , 34 , 36 , 37 ] in vivo.…”
Section: Depurination Assaysmentioning
confidence: 99%
“…The contribution of toxin-ribosome interactions to the depurination activity of RIPs was determined by comparing the activity of mutants on ribosomes and an SRL mimic RNA, since depurination activity on rRNA does not require ribosome binding [ 31 , 34 , 35 , 36 , 37 ]. Using the qRT-PCR and the enzymatically-coupled adenine detection assay, mutants defective in ribosome binding, but not catalytic activity were identified and ribosome-binding site of RTA and Stxs were mapped to the distal face of the active site [ 31 , 34 , 35 , 36 , 37 ]. These assays showed that the interaction of Stxs and RTA with the stalk proteins has a profound effect on their catalytic efficiency towards the SRL [ 34 , 36 , 37 , 89 ].…”
Section: Contributions Of the Different Assays To Measure Activitymentioning
confidence: 99%
See 1 more Smart Citation